Present and Future Actions of CETYS University to Mitigate Climate Action - Azuz-Adeath, Isaac; Aguiar, Fernanda; Valdes, Adrian; Lopez, Ulises (Universitas Diponegoro, 2024)
The strategic location of CETYS University, in Baja California state in the northwest of Mexico, gives it exceptional conditions for the use of renewable energies. With an installed photovoltaic solar energy capacity of 1.37 MW, it is the academic institution with the greatest generation potential in Latin America. The importance that CETYS University gives to the subject has stimulated the institution since 2015 to offer a degree and master's degree in renewable energy to have greater and better collaboration with solar and wind energy technology companies located in the state. With a vision of the future, in 2023 the CETYS Institute for Sustainability Studies (ISS) was created to promote and coordinate, among other actions, those related to energy and climate change. With a planning horizon until 2036, the ISS, looking forward, has proposed the following actions: a) an internal audit to increase the energy efficiency of their buildings and classrooms; b) support for research projects to build on-campus operational small-scale wind energy systems; c) the deployment of the 300 x 500 program, which seeks to plant at least 300 native trees in the region with low water consumption each year, to offset the atmospheric emissions of 500 vehicles; d) a policy to achieve 80% carbon neutrality, and e) the incorporation of CETYS to the network of Mexican universities for climate action. Among many others, these actions position CETYS as a leading institution in sustainable development at the regional level.